Therapeutic Interventions using Monotherapy versus Combination Therapy of Aloe vera and Omega-3 Fatty Acids on Gentamicin-initiated Renal Toxicity via Attenuation of Renal Biomarkers - Maheshwari, Rajesh A.; Kaur, Gurpreet; Sen, Dhanya B.; Parmar, Ghanshyam; Balaraman, Ramachandran; Seth, Avinash K.; Sen, Ashim K. (Indian Journal of Pharmaceutical Education and Research, 2021)
Background and Aim: The proposed work was planned to evaluate the potential protective role of aqueous Aloe vera (AV) concentrate and/or Omega-3 fatty acids (O3FAs) against GM -initiated renal toxicity in rats. Materials and Methods: Thirty female Wistar-albino rats were distributed into five equivalent groups as follows: Normal control group, GM control group, GM + AV group (200 mg/kg, p.o.), GM + O3FAs group (100 mg/kg, p.o.), GM + AV + O3FAs group. All the treatments were administered for 10 days. Renal toxicity was initiated by intraperitoneal administration of GM (80 mg/kg/day) for last 5 days of test duration. Results: Noticeable rise in the levels of serum creatinine, urea, MDA, TNF-α, TGF-β1, Fibronectin and NGAL was seen alongside a significant decrese in the levels of serum albumin, total protein content and antioxidant enzymes, SOD, GSH, catalase in GM control group. Treatment with AV or O3FAs or AV + O3FAs exhibited a considerable reduction in serum creatinine, urea, MDA, TNF-α, TGF-β1, Fibronectin and NGAL levels and a rise in the levels of serum albumin, total protein and antioxidant enzymes. Conclusion: The study concluded the importance of AV and Omgea-3 fatty acids as effective nephroprotective agents. However, the combined treatment with AV and O3FAs showed similar beneficial effects as compared to monotherapy in mitigating adverse effects of GM-initiated renal toxicity. There was no significant difference observed in monotherapy as well as combination therapy.
Keywords: Aloe vera; Gentamicin; Omega-3 fatty acid; TGF-β1; Fibronectin; NGAL